Pengaruh Infusa Daun Sambiloto (Andrographis paniculata Nees) Terhadap Pertumbuhan Bakteri Shigella dysenteriae Secara In Vitro - Fitri Nadifah (LPPM STIKES Guna Bangsa Yogyakarta, 2014)
Background: Bacteria Shigella dysenteriae is pathogenic bacterium which cause diarrheal diseases that enter into inside the body through intestine. Shigella dysenteriae constitute one of the gram negative bacterium which causes inflammation on intestinal, pain abdominal, tenesmus, and a bowel movements which accompanied with blood and mucus. Bad impact irational use of synthethic drugs and antibiotics can cause organ damage and germs resistance. Utilization of herbs as traditional medicine evolving rapidly and alternatively used by most. Traditional medicine has relatively low of side effect and affordable prices. Sambiloto (Andrographis paniculata Nees) is a plant which is ordinary used as a traditional medicine that can easily found around Indonesian islands. Sambiloto constitute one of the medicinal plants which is allegedly has the antibacterial effect because its chemical content of flavonoid saponins and tannin.